SELF-ACCEPTANCE PROCESS FOR VICTIMS OF SEXUAL VIOLENCE IN YOUTH AT THE WOMEN'S SOLIDARITY FOUNDATION FOR HUMANITY AND HUMAN RIGHTS (SPEK-HAM) SURAKARTA - Rima Faiqotul Affa; Ita Rodiah (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
The occurrence of cases of violence is a problem that often occurs in women, not only among adults but also among teenagers and minors. The number of sexual violence in Indonesia is increasing every year so that from time to time it has increased more rapidly than in previous years, often occurring around the victim or even the victim's own relatives. The forms of violence that occur are not only pursuing violence but also forms of sexual violence, children who get sexual forms usually do not respond to their parents towards their environment and society considers sexual violence to be a deviant personality. This study uses a qualitative method with the subject of 2 teenagers who are still in school including class X and class XI. Data were collected by unstructured interviews and observation of victims using a sampling technique. the validity of the data using triangulated data and using triangulation sources to check the sharing of data into conclusions. The results of the research on the process of self-acceptance of victims of sexual violence in adolescents at the SPEK-HAM foundation have 4 stages, namely the rejection stage, the tolerance stage, the enabling stage, the friendship stage with the following characteristics of a strong self, striving for positive things, being comfortable with oneself, able to accept criticism and suggestions.